2014
DOI: 10.5551/jat.21212
|View full text |Cite
|
Sign up to set email alerts
|

Association between the CHADS2 Score and an Ankle-Brachial Index of <0.9 in Patients without Atrial Fibrillation

Abstract: Aim:The ankle-brachial index (ABI) is an easy-to-use, non-invasive and reliable diagnostic tool for assessing peripheral arterial occlusive disease (PAOD). The CHADS2 (congestive heart failure, hypertension, age ≧75 years, diabetes, prior stroke) score is a simple and popular clinical parameter that is used to assess the risk of stroke in patients with atrial fibrillation (AF). Because all five components of the CHADS2 score are risk factors for PAOD, the score should have a strong correlation with the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(49 reference statements)
0
12
0
2
Order By: Relevance
“…In addition, Welles et al showed that the score can be used to predict ischemic stroke/transient ischemic accident in non-AF subjects with coronary heart disease 12) , and Chao et al demonstrated that a high CHADS2 score is associated with an increased risk of new-onset AF in non-AF patients 13) . Furthermore, our recent cross-sectional study confirmed a significant association between the CHADS2 score and PAOD, as indicated by an ABI of 0.9, in non-AF patients 14) . In the present study, we further found that a twopoint increment in the CHADS2 score was associated with a 2.51-fold risk of new-onset PAOD in the non-AF patients.…”
Section: Incidence Of Paod In Taiwanmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, Welles et al showed that the score can be used to predict ischemic stroke/transient ischemic accident in non-AF subjects with coronary heart disease 12) , and Chao et al demonstrated that a high CHADS2 score is associated with an increased risk of new-onset AF in non-AF patients 13) . Furthermore, our recent cross-sectional study confirmed a significant association between the CHADS2 score and PAOD, as indicated by an ABI of 0.9, in non-AF patients 14) . In the present study, we further found that a twopoint increment in the CHADS2 score was associated with a 2.51-fold risk of new-onset PAOD in the non-AF patients.…”
Section: Incidence Of Paod In Taiwanmentioning
confidence: 63%
“…In addition, several studies have reported that the CHADS2 score can be used to predict subsequent cardiovascular events and new-onset AF in non-AF populations [11][12][13] . As an older age, hypertension, diabetes, congestive heart failure and stroke are all risk factors for PAOD [1][2][3][4][5][6][7] , our recent cross-sectional study demonstrated that the CHADS2 score is significantly associated with an ankle-brachial index (ABI) of 0.9 in non-AF patients 14) . However, divided the study patients into four groups: group 1 (score 0), group 2 (score 1-2), group 3 (score 3-4) and group 4 (score 5-6).…”
Section: Data Sourcementioning
confidence: 99%
“…In the last few years, use of the CHADS 2 score has extended beyond the original scenario of atrial fibrillation, 14,15 and it has shown certain advantages over other methods (SCORE or Framingham criteria), such as inclusion of older patients and greater ease of use in daily practice. Henriksson et al applied this score to a large series of stroke survivors included in the Swedish Stroke Registry and reported that the risk of death due to a cerebral event at 5 years showed a progressive, linear increase in parallel with the CHADS 2 score, in both patients with atrial fibrillation and those in sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…La puntuación CHADS 2 4 se desarrolló originalmente como un esquema de predicción del riesgo de ictus en los pacientes con fibrilación auricular no valvular 1,3 . Sin embargo, en los últimos años se ha extendido su uso más allá de su escenario original de la fibrilación auricular 16,17 , y presenta algunas ventajas sobre otras escalas (SCORE o Framingham), como la inclusión de pacientes de más edad y su menor complejidad en su utilización diaria. Henriksson et al han aplicado esta puntuación a una amplia serie de pacientes supervivientes a un ictus incluidos en el Swedish Stroke Registry, y demuestran que el riesgo de mortalidad a los 5 años del episodio cerebral aumenta gradual y linealmente con la puntación del CHADS 2 , tanto para pacientes con fibrilación auricular como en ritmo sinusal 18 .…”
Section: Discussionunclassified